CT support of cardiac structural interventions - Hell, Michaela M.; Achenbach, Stephan (British Journal of Radiology, 2019)
Due to its high temporal and isotropic spatial resolution, CT has become firmly established for pre-procedural imaging in the context of structural heart disease interventions. CT allows to very exactly measure dimensions of the target structure, CT can provide information regarding the access route and, as a very valuable addition, volumetric CT data sets can be used to identify fluoroscopic projection angulations to optimally visualize the target structure and place devices. This review provides an overview of current methods and applications of pre-interventional CT to support adult cardiac interventions including transcatheter aortic valve implantation, percutaneous mitral valve intervention, left atrial appendage occlusion and paravalvular leak closure.
CRIS-Team WoS Importer:2019-06-07